Role of Biodiversity International in agricultural and horticultural research in India - Kumar, N. K. Krishna; Hanchinal, R. R.; Gupta, Arnab; Dandin, S. B. (Indian Farming, 2018)
The study on the effect of diversity of pollinator, natural enemies and soil arthropods will also include metaanalytical approaches that draw upon and strengthen existing research. This data will be used to develop predictive and iterative models of response to particular groups and their ecosystem services. The model will then be used to develop improved management interventions for testing and scaling with farming communities. Enhancing genetic resources of soybean and its pre-breeding for soybean improvement programme in India. Implement of GEF project ‘Mainstreaming agro-biodiversity conservation and utilization in agricultural sector to ensure ecosystem services and reduce vulnerability’ across 14 sites in India. Continuation of training programmes in partnership with NBPGR. In vitro and cryopreservation training course, and Genebank Operations and Advanced Learning (GOAL) Master Class to be continued for an all round synergy of the international exposure of Bioversity International and the robust and wide research spread of ICAR.